Efisiensi Usahatani Padi (Oryza Sativa) Di Dusun Menganti Desa Karangsemanding Kecamatan Balongpanggang Gresik - Irvan Maulana; Garist Sekar Tanjung; R. Achmad Djazuli (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Indonesia is known as an agricultural country, making the agricultural sector very important with the commodity most widely cultivated by the public being rice. Karangsemanding Village is a village that has extensive agricultural land but has a small productivity value compared to other villages. This research aims to determine the factors that influence the production of lowland rice farming and determine the efficiency of lowland rice farming in Menganti Hamlet. The research was conducted in Menganti Hamlet in June-September 2023. Data collection was carried out through interviews and questionnaires as well as secondary data obtained. The sampling technique was saturated sampling which involved all members of the population sampled as many as 86 farmers. Data were analyzed descriptively and in multiple linear regression analysis with the help of SPSS software. The research results show that production factors in the form of land area, seeds, fertilizer, pesticides and labor simultaneously influence rice production, while partially the variables of land area, pesticides and labor have a significant influence on production. The results of the technical efficiency analysis show a value of 0.8894 which is said to be efficient in the use of production factors because it is close to 1. Judging from the price efficiency (allocative) of lowland rice farming, it shows a value of 0.0416, this shows that lowland rice farming in Menganti Hamlet is not yet efficient economically. price. Meanwhile, the economic efficiency of lowland rice farming shows a value of 0.0370, which means lowland rice farming is economically inefficient..